Evaluasi efektivitas skrining non-invasif untuk deteksi dini gangguan kaki pada diabetisi - Atun, Sri; Sofiani, Yani; Jumaiyah, Wati; Rayasari, Fitrian; Yunitri, Ninik (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Diabetic neuropathy is a complication that develops slowly and often goes undiagnosed. Guttormsen explained that neuropathy usually appears after years of diabetes and is often the initial cause of wounds and amputations. Therefore, early detection is crucial to prevent further complications. One recommended approach is non-invasive screening, which allows for early identification before severe symptoms appear. Purpose: To evaluate the effectiveness of non-invasive screening for early detection of foot disorders in people with diabetes. Method: The implementation of evidence-based nursing practice (EBNP) at Al Ihsan Regional Hospital, West Java Province, from June to July 2025, involved a non-invasive screening intervention for each patient for early detection of foot disorders in diabetic patients. This study was preceded by a systematic review and meta-analysis that compiled data from various previous studies. Results: Participants with the ROC curve test showed screening results on BDRFS with a sensitivity value of 1.000; on monofilament screening the sensitivity value was 0.545; vibration screening test sensitivity value was 0.818; temperature screening test sensitivity value was 0.864. In the QST screening test of touch sensation, it showed that the temperature screening test sensitivity value was 0.909. The QST screening test of vibration sensation showed that the temperature screening test sensitivity value was 0.909. The QST screening test of temperature sensation showed that the temperature screening test sensitivity value was 0.773. Conclusion: The implementation of EBNP “Evaluation of the Effectiveness of Non-Invasive Screening for Early Detection of Foot Disorders in Diabetics” has been proven to significantly increase early detection of diabetic neuropathy through a method that is safe, inexpensive, and can be performed by nurses. Keywords: Diabetes; Early Detection of Foot Disorders; Non-Invasive Screening. Pendahuluan: Neuropati diabetik merupakan komplikasi yang berkembang secara perlahan dan sering kali tidak terdiagnosis secara dini. Guttormsen menjelaskan bahwa neuropati biasanya muncul setelah bertahun-tahun menderita DM dan sering kali menjadi penyebab awal terjadinya luka hingga amputasi. Untuk itu, deteksi dini sangat penting guna mencegah komplikasi lebih lanjut. Salah satu pendekatan yang direkomendasikan adalah skrining non-invasif, yang memungkinkan identifikasi dini sebelum muncul gejala berat. Tujuan: Untuk mengevaluasi efektivitas skrining non-​​invasif untuk deteksi dini gangguan kaki pada diabetisi. Metode: Penerapan praktik keperawatan berbasis bukti (Evidence Based Nursing Practice/EBNP) yang dilaksanakan di RSUD Al Ihsan Provinsi Jawa Barat pada bulan Juni-Juli 2025. Setiap pasien dilakukan intervensi berupa pemeriksaan skrining non-invasif untuk deteksi dini gangguan kaki pada pasien diabetes. Hasil: Partisipan dengan uji ROC curve menunjukkan hasil skrining pada BDRFS dengan nilai sensitivity 1.000; pada skrining monofilamin nilai sensitivit 0.545; skrining vibrasi test nilai sensitivity 0.818; skrining temperatur test nilai sensitivit 0.864. Pada uji skrining QST sensasi sentuhan menunjukkan bahwa skrining temperatur test nilai sensitivit 0.909. Uji skrining QST sensasi getaran menunjukkan bahwa skrining temperatur test nilai sensitivit 0.909. Uji skrining QST sensasi suhu menunjukkan bahwa skrining temperatur test nilai sensitivit 0.773. Simpulan: Penerapan EBNP “evaluasi efektivitas skrining non-invasif untuk deteksi dini gangguan kaki pada diabetisi” terbukti dapat meningkatkan deteksi dini neuropati diabetik secara signifikan melalui metode yang aman, murah, dan dapat dilakukan oleh perawat. Kata Kunci: Diabetisi; Deteksi Dini Gangguan Kaki; Skrining Non-​​Invasif.